2009
DOI: 10.2176/nmc.49.162
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cavernous Hemangiomas of the Skull Associated With Hepatic Lesions -Case Report-

Abstract: A 55-year-old woman presented with multiple calvarial cavernous hemangiomas manifesting as right frontal swelling. Craniography and computed tomography showed an osteolytic lesion. Magnetic resonance imaging demonstrated multiple intraosseous lesions, and radioisotope bone scintigraphy identified even more numerous lesions. Total resection of the right frontal lesion and cranioplasty was performed. Histological examination confirmed the lesion as a cavernous hemangioma. Computed tomography of the abdomen revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
6
0
3
Order By: Relevance
“…It constitutes 0.5% to 1.0% of all bone tumors. [4][5][6] Hemangiomas of the head and neck are benign vascular lesions, and although they are common in these regions but it occurs rarely in paranasal sinuses. Fu et al reported in his study 85 cases of vascular tumors of which angiofibroma was the most number of occurring tumour followed by capillary haemangioma and 5 cases of cavernous haemangioma and the other vascular tumours.…”
Section: Discussionmentioning
confidence: 99%
“…It constitutes 0.5% to 1.0% of all bone tumors. [4][5][6] Hemangiomas of the head and neck are benign vascular lesions, and although they are common in these regions but it occurs rarely in paranasal sinuses. Fu et al reported in his study 85 cases of vascular tumors of which angiofibroma was the most number of occurring tumour followed by capillary haemangioma and 5 cases of cavernous haemangioma and the other vascular tumours.…”
Section: Discussionmentioning
confidence: 99%
“…5 The cause is thought to be congenital, 2,24 although heredity and family history are not noted. 3 Trauma is considered to be the most important etiology of this tumor. 2,5 In the case under discussion, there was a history of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, a link to family occurrences suggests an autosomal dominant interaction with low penetration. 3 In most cases, surgical intervention is not required. When removal is necessary, 2,4 excision under local anesthesia with simple repositioning of the flap is the accepted course of action.…”
Section: Abstract: Exostoses Surgery Oralmentioning
confidence: 99%
“…El diagnóstico diferencial incluye la displasia fibrosa, osteoma, histiocitosis de células de Langerhans, meningioma, enfermedad metastásica, tumor dermoide y mieloma múltiple 18 .…”
Section: Figura 2 (A) Secuencia T2 De La Resonancia Magnética De Cráunclassified
“…Pilcher reportó la primera exéresis exitosa de un hemangioma del cráneo en 1894 3 . En 1923 Cushing reporto la resección en bloque del tumor con un borde de hueso normal 18 . El tratamiento quirúrgico de elección es la exéresis en bloque 2 , esta técnica disminuye la pérdida sanguínea transoperatoria aunque esto no sea posible cuando se encuentra involucrada la base del cráneo 17 .…”
Section: Figura 2 (A) Secuencia T2 De La Resonancia Magnética De Cráunclassified